COMPUTATIONAL AND ANALYTICAL MODELS FOR EQUATIONS OF PARABOLIC TYPE WITH APPROXIMATE DATA ON THE BASIS OF METHODS OF APPLIED HARMONIC ANALYSIS AND VARIATIONAL METHOD OF WEIGHTED RESIDUALS - Igor Eduardovich Naats; Victoria Igorevna Naats; Roman Andreyevich Ryskalenko (Наука. Инновации. Технологии)
Considered non-stationary equation of mass transfer of impurities in the atmosphere, which is a linear differential equation of parabolic type. It is assumed that the mathematical model requires attracting approximately given initial data or semiempirical functions for their determination. To solve this problem in the work builds regulating numerical methods and related computational and analytical models based on the methods of applied harmonic analysis and variational method of weighted residuals.